2011
DOI: 10.1007/s00244-011-9693-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of Polycyclic Aromatic Hydrocarbons (PAHs) in Bile as Biomarkers of Pollution in European Eel (Anguilla anguilla) from German Rivers

Abstract: In the light of the alarming decline of the European eel (Anguilla anguilla L.) population, there is an urgent need to define ecological indicators for eel habitat quality. Due to an increasing shortage of glass eels available for local stock enhancement, the decision of whether restocking is a valuable management tool to increase high-quality silver eel escapement to the sea needs to be evaluated. Organic contaminants, such as polycyclic aromatic hydrocarbons (PAHs), are among the major threats to fish in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The mean PAH metabolite concentrations in eel from European countries (range of means; 1-OHPyr: 56-3200 ng mL −1 ; 1-OHPhe: 70-495 ng mL − 1 ) are in the same order of magnitude than those found in P. vachellii obtained in this study (means: 1-OHPyr: 1087 ng mL − 1 ; 1-OHPhe: 136 ng mL − 1 ) Nagel et al, 2012;Ruddock et al, 2003;Szlinder-Richert et al, 2014).…”
Section: Pah Metabolites In Bile Of P Vachelliimentioning
confidence: 47%
“…The mean PAH metabolite concentrations in eel from European countries (range of means; 1-OHPyr: 56-3200 ng mL −1 ; 1-OHPhe: 70-495 ng mL − 1 ) are in the same order of magnitude than those found in P. vachellii obtained in this study (means: 1-OHPyr: 1087 ng mL − 1 ; 1-OHPhe: 136 ng mL − 1 ) Nagel et al, 2012;Ruddock et al, 2003;Szlinder-Richert et al, 2014).…”
Section: Pah Metabolites In Bile Of P Vachelliimentioning
confidence: 47%
“…At the same time, a movement of eels even in the yellow eel stage is another possible explanation for the detected results. In accordance with Nagel et al (2012a) and Ruddock et al (2003) 1-OH-Pyr was found to be the dominant compound in eel bile, except in samples from ''Sebou up'' where both metabolites are present in nearly equal concentrations (Table 1). Comparing the results of the present study to similar investigations from several European countries (Table 2), it is shown that the means of both PAH metabolite concentrations, especially in eel from the United Kingdome and Germany are higher compared to concentrations found in eel from Morocco.…”
Section: Bull Environ Contam Toxicolmentioning
confidence: 81%
“…Since eels are quite heavily exploited in Moroccan inland waters (ICES 2011), a pollution assessment is needed, not only with regard to thresholds for human consumption but also to detect possible biological effects of contaminants on this species. Although some studies exist on PAH metabolites in eel Nagel et al 2012a;Ruddock et al 2003;SzlinderRichert et al 2014) up to now no data are available for PAH metabolites in fish from Moroccan waters. The aim of this study was to bridge this gap and to provide first information on concentrations of PAH metabolites of eels in Morocco; to evaluate spatial differences in PAH contamination and to discuss the possible threat for eel due to PAH contamination.…”
mentioning
confidence: 99%
“…PAH metabolites as biomarker has been determined in a variety of marine, estuarine and fresh water fish species, such as English sole (Collier and Varanasi, 1991), plaice (Richardson et al, 2004), flounder (Ariese et al, 1993;Beyer et al, 1996;Eggens et al, 1996;Kopecka et al, 2006;Vethaak et al, 2011), dab (Kammann, 2007;Vethaak et al, 2009), Atlantic cod (Beyer et al, 1996;Aas et al, 2000), Atlantic hagfish (Sundt et al, 2011), feral finfish (Hellou et al, 2006), eelpout (Tairova et al, 2012), brown bullhead (Yang and Baumann, 2006), trout (Escartín and Porte, 1999a), eel (Van der Oost et al, 1994;Ruddock et al, 2003;Gorbi and Regoli, 2004;Nagel et al, 2012;Kammann et al, 2014), and red mullet (Escartin and Porte, 1999b;Martínez-Gómez et al, 2013). The concentration of PAH metabolites in the bile fluid with dab and flounder as target species has become part of international monitoring programmes, such as the OSPAR Joint Assessment and Monitoring Programme (JAMP) (OSPAR Agreement 2008-09; Technical Annex 2: PAHspecific biological effects monitoring; OSPAR, 2008).…”
Section: Introductionmentioning
confidence: 99%